2007
DOI: 10.1086/510072
|View full text |Cite
|
Sign up to set email alerts
|

Can Routine Clinical Markers Be Used Longitudinally to Monitor Antiretroviral Therapy Success in Resource‐Limited Settings?

Abstract: Although routine clinical markers are used routinely to determine the stage of human immunodeficiency virus (HIV) disease, their use in monitoring response to antiretroviral therapy is poorly defined. Selected clinical markers were evaluated for their ability to predict first-line antiretroviral therapy success. No clinically meaningful variables were identified that predicted virologic or immunological success, implying that the CD4+ cell count and HIV type 1 RNA level data are required for optimal management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 10 publications
0
37
0
Order By: Relevance
“…Akileswaran and others suggested that the frequency of CD4 cell count monitoring of patients to be every 6 months (25). Other study proposed CD4 cell counts determination to be as often as monthly to every 3 months (27). The hospital had only one machine for CD4 determination which breaks frequently; otherwise according to the Ethiopian guideline it could have been done every 6 months.…”
Section: Discussiomentioning
confidence: 99%
“…Akileswaran and others suggested that the frequency of CD4 cell count monitoring of patients to be every 6 months (25). Other study proposed CD4 cell counts determination to be as often as monthly to every 3 months (27). The hospital had only one machine for CD4 determination which breaks frequently; otherwise according to the Ethiopian guideline it could have been done every 6 months.…”
Section: Discussiomentioning
confidence: 99%
“…Incomplete VL suppression during therapy leads to the emergence and evolution of drug resistance, reducing treatment options and resulting in the transmission of resistant mutants (7). Neither clinical findings nor CD4 cell counts are adequate predictors of viral suppression, and in fact management by CD4 cell counts alone can lead to unnecessary treatment changes (1). VL testing is the only reliable marker for the early detection of the failure of antiretroviral therapy (17,20).…”
mentioning
confidence: 99%
“…Optimal clinical outcomes require maximal suppression of viral replication with combination therapy, and current World Health Organization recommendations to assess adherence, clinical findings, and changes in CD4 cell count cannot predict virologic HAART failure [43,44]. In addition, drug-resistant HIV infection represents a real public health threat, because the transmission of such infection limits the usefulness of certain HAART regimens.…”
mentioning
confidence: 99%